Silagem pré-secada de cereais de inverno com ou sem uso de aditivos - Cerutti, Weiler Giacomazza (2018)
Aiming to evaluate the productivity of white oat, barley and wheat, as well as their nutritional composition, fermentative parameters and aerobic stability when stored as pre-dried, harvested in two phenological stages, and, whether subjected or not to the use of biological additives, it was conducted an experiment at the north area from Rio Grande do Sul, with sowing in June and harvest between August and September of 2017; moments in which these cereals, respectively, were on vegetative and reproductive stages. After harvest, the cereals were exposed to the sun in order to achieve 30 to 35% of dry matter, and they were treated with, or without, the use of enzymatic bacterial inoculant and / or propionic acid, before being packed with six layers of plastic film, with 50% overlap in bales of approximately 50 kg. After 45 days of storage, the samples were taken and homogenized for further evaluation of pH and bromatological composition. To evaluate aerobic stability, 4 kg of silage were placed in trays and transferred into a room at a temperature of 24 ± 1oC, where the material temperature was measured 6 times a day for 5 days. Oat and barley presented the highest yields with 5,033 and 7,079 kg of dry matter per hectare, respectively, whereas wheat produced 3.722 Kg/ha of dry matter. The cereals at vegetative stage obtained, respectively, lower yields in relation to the cut at reproductive stage, 3.479 kg and 7.645 kg dry matter per hectare. It was not possible to observe differences considering bromatological variables, when the enzymatic bacterial inoculant or the propionic acid were added to the cereals. However, when the cut was performed at the vegetative stage, it was possible to obtain pre-dried material with higher protein percentages, lower NDF, FDA and lignin, and higher NDF digestibility values at 30 hours. The best evaluations of milk production per ton of dry matter were observed for barley at the reproductive stage. The addition of inoculant containing homo and heterofermentative bacteria provided higher values of lactic acid, lower pH values and lower losses through ammoniacal nitrogen in the cereals. When we evaluated the addition of propionic acid, it was observed that the additive was not able to improve the fermentative parameters when compared to the control group. The ammoniacal nitrogen was influenced by the amount of water present in the cereals, when the cereals presented low values of dry matter, the N-NH3 values were higher. The aerobic stability was not influenced by the addition of additives or by the phenological stage. Among the cereals, the wheat, after being exposed to air, was the one which presented lower stability.